Assessment of Spiritual Attitude in Madrasah: Multicase Study in Lamongan, East Java, Indonesia - Raikhan Raikhan (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
The purpose of this study is to describe, understand, and analyze the implementation of the assessment in the spiritual attitudes in madrasas? This question is detailed into several units of questions about principles, purposes, indicators, techniques, and the utilization of spiritual attitude assessment in madrasas. This study used a qualitative approach, taking three cases on the research subject or three madrasas in Lamongan Regency. The instruments used in this research were structured and unstructured interviews, document studies, and observations. As for data validation in this study, triangulation of data sources and methods was used, which were then analyzed. The authors' findings on the assessment of spiritual attitudes in madrasas could be concluded that attitude assessment was carried out using the implicit method, measuring without asking students directly. This was developed to overcome bias and pretense. In principle, according to As Syaibani's philosophy of Islamic education, the result of education is an interaction between science, charity, and faith. The assessment purposes according to the Assessment as Learning (AaL) approach, assessment as muhasabah, education, and motivation. The indicators and assessment criteria were in three aspects including ritualistic, experiential, and consequential, or the spiritual, insaniyyah, and kauniyyah dimensions, while the instrument used was a non-test instrument, which was used for performance or behavior assessment, as for the management and utilization elements of the results. The assessment used more ethical references or Value Reference Assessment with the assumption that human nature was good, education functions to develop nature. Keywords: attitude assessment; spiritual attitude; madrasa